Organizational Commitment Matters More than Supervision in Nursing Documentation Compliance - Suryanti Suryanti; Supriyantoro Supriyantoro; Idrus Jus’at (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Nursing care documentation is crucial for service quality and patient safety, but incomplete and inconsistent documentation remains a challenge in hospitals. This study focuses on nurses at Medika Lestari Hospital, where documentation compliance is below expectations. The aim is to analyze how organizational commitment and supervision affect nursing care documentation, with work motivation as an intervening variable. A quantitative cross-sectional design with a structural model approach was used, and data were collected via structured questionnaires and analyzed using SEM-PLS. The results show that organizational commitment positively impacts documentation compliance (β = 0.268; p = 0.013), highlighting the importance of nurses’ attachment to organizational goals. Supervision, however, has no significant direct effect on documentation (β = 0.220; p = 0.109). Both organizational commitment (β = 0.285; p = 0.018) and supervision (β = 0.382; p = 0.000) significantly influence work motivation, indicating that managerial control and organizational attachment contribute to motivation. However, work motivation does not significantly affect documentation (β = 0.231; p = 0.053) and does not mediate the effects of commitment or supervision on compliance. In conclusion, improvements in documentation are primarily driven by organizational commitment rather than motivational or supervisory factors. Hospital management should focus on enhancing nurses’ organizational commitment and aligning supervisory practices with institutional values to improve documentation compliance sustainably.